Comparing Glucagon-Like Peptide-1 Receptor Agonists to Sodium-Glucose Cotransporter-2 Inhibitors in Heart Failure With Preserved Ejection Fraction: A Systematic Review - Al-Shudifat, Moath; Sumra, Bushra; Kocherry, Cyril; Shamim, Hina; Jhakri, Kiran; Khan, Safeera (Curēus (Palo Alto, CA), 2025)
Heart failure with preserved ejection fraction (HFpEF) is a subtype of congestive heart failure distinguished by a normal ejection fraction. Comorbidities associated with its development typically include chronic conditions such as diabetes, hypertension and obesity that restrict the heart's filling pressure. Since heart failure with reduced ejection fraction (HFrEF) has been the subject of much research, physicians have always been faced with the problem of a lack of effective therapeutic interventions when treating patients with HFpEF. In recent years, there has been an increase in the number of research studies to identify effective therapeutic medication for HFpEF. Sodium-glucose cotransporter-2 (SGLT-2) inhibitors and glucagon-like peptide-1 (GLP-1) receptor agonists, which were initially developed to manage diabetes, have shown improvement in clinical outcomes in HFpEF even in the absence of diabetes. This systematic review aimed to gather and analyze evidence from randomized controlled trials and observational studies on the two drug classes. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines were followed in the conduct of this comprehensive systematic review. To find all relevant studies, we searched three major medical databases, including Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), and PubMed (NCBI). We have identified 13 studies on both classes of drugs, some of which have contributed to formulating current guidelines for managing HFpEF. The quality of included studies has been scrutinized using quality assessment tools, including the Cochrane Risk of Bias 2 tool and the Newcastle-Ottawa Scale tool, to ensure transparency and limit bias to lead to more reliable findings. Most studies on SGLT-2 inhibitors demonstrated a significant reduction in hospitalization rates and symptom burden, as measured by Kansas City Cardiomyopathy Questionnaire (KCCQ) scores and functional capacity, as measured by a 6-minute walk test distance. GLP-1 receptor agonists have also improved symptom scores and functional capacity, specifically in obese patients, although reductions in hospitalization rates remain unclear. Improvements in functional capacity and symptom scores were observed for both drug classes, though some metrics were not consistently statistically significant across studies. The superiority of one medication over another remains inconclusive due to a lack of trials comparing both drugs. In addition, GLP-1 receptor agonists have been more recently studied, necessitating further research on this drug class to assess long-term outcomes, efficacy in non-obese patients, and combination with SGLT-2 inhibitors.